Durability performance of ultra-high performance concrete (UHPC) incorporating waste rubber powder - Syed Mohamad Arzmierull, Syed Nasruddin (2017)
Solid waste disposal from waste by-products are one of the major environmental issue nowadays such as tires disposal. Previously, the utilization of recycled tires as aggregate replacement in conventional concrete production have been explored. In comparison, ultra-high performance concrete (UHPC) is introduce in this present study. Nowadays, UHPC has become famous due to it high strength that can achieved up to 100 MPa. Besides, UHPC was produced by using low water cement ratio and replacing the OPC with 10% silica fume improved significantly its workability, strength and durability. Therefore, an idea to replace the amount of fine aggregate with waste tires namely micronized rubber powder (MRP) in UHPC production was studied. The levels replacement of MRP comprises of 5%, 10% and 15% from the weight of fine aggregate used. In this present study, the effect of using different percentage of MRP to the UHPC properties subjected to durability resistance was investigated. For durability test, the UHPC specimens were immersed in hydrochloric acid solution and magnesium sulphate solution for 14, 28 and 60 days of exposure. After immersion, the exposed specimens were tested to determine the strength and its mass loss respectively. From the result, UHPC with WRP were highly resist towards acid and sulphate attack. This study had proved the rubber in UHPC had drastically reduce in compressive strength but still stronger than ordinary concrete. It is hope that, this study could be useful for future innovation with the use of waste rubber in construction industry.